Problem of Professional Self-Determination Formation and Person’s Professional Typology Construction - O. A. Kolosova (Управление, 2016)
This paper is based on the results of research related to a problem of professional self-determination formation and person’s professional typology construction, and devoted to how the knowledge of students’ individual-psychological and social-psychological features will allow during training in higher education institution not only adequately use natural tendencies and abilities, but also to help in formation of activity’s individual style allowing to compensate a lack of some components development by development of others ones. As a result this will allow solve effectively the same professional problems by people with various combination of operational components in person’s structure. Therefore in this case it is appropriately to focus attention on the typological approach to person’s features similarity studying under the profession influence, and, taking this approach as a basis, a more flexible studying of this problem is offered, assuming the possibility for existence of several types in the same professional community. Therefore, there is an opportunity for dynamic development of person’s qualities in the presence of strongly expressed motivation to professional activity.This direction of researches is especially topical in connection with political and social-economical transformations in society, and introduction of professional standards, demanding essential changes in training of specialists. Nowadays there is rather serious gap between employers’ requirements in the labor market, and knowledge and skills which are gained by graduates during the training. The professional standards regulating requirements to work’s quality and content and being an obligatory element for an assessment of graduate’s training quality and his readiness for the future professional activity only describe necessary parameters, without answering a question how these parameters may be created at the youth choosing the certain profession, taking into account person’s specific features. If the person’s professional choice is defined by random factors and there is no activity’s individual style formation during the training, such mistakes will be cost much in the future to both the person and the higher education institution.